An overview of gamasoidosis caused by Ornithonyssus bursa (Mesostigmata: Macronyssidae) in Brazil and new case records - Mesquita-Sousa, Dauana; Viegas-Melo, Davi; Martins, Thiago F.; Monteiro, Silvia G.; Faccini, João L. H.; Labruna, Marcelo B.; Barros-Battesti, Darci M. [UNESP]; Bassini-Silva, Ricardo; Soares, Alexandra M. S.; Costa-Junior, Lívio M.; Luz, Hermes R. (Taylor & Francis, 2020)
Ornithonyssus bursa: is a haematophagous mite of veterinary and public health concern. The association between O. bursa and humans in Brazil has been known for several decades, but most of the information is limited and confusing. Herein, we present an overview of the cases of gamasoidosis in Brazil based on published and new records. Wild birds are common sources for human infestation, especially omnivorous and insectivorous birds that live in urban and rural environments. Species of the Columbidae are the most common birds associated with O. bursa in Brazil.
Keywords: Amazon; birds; Brazil; ectoparasites; mites; northeast